HOW PROSTATE TUBERCULOSIS IS DIAGNOSED - S. Yu. Shevchenko; V. V. Potapov (Вестник урологии, 2017)
Introduction. Prostate tuberculosis is not rare, but often overlooked disease: 77% of patients died from tuberculosis any localization had prostate tuberculosis and mostly it was not diagnosed alive; in 25% of patients with pulmonary tuberculosis prostate tuberculosis was revealed by biopsy. Material and Methods.History cases of out-patients with prostate tuberculosis who was under observation in the Novosibirsk tuberculous dispensary in 2010-2015 years were analyzed retrospectively with purpose to estimate the ways of the diagnosis of prostate tuberculosis. Results. More often (41.7%) reason to suppose prostate tuberculosis was chronic prostatitis resistant to standard therapy. In 18.1% the disease was accidental finding after surgery due to benign prostatic hyperplasia (5.6%) or in time of examination patients with pulmonary tuberculosis (12.5%), who had no prostate-specific symptoms.Conclusion. Prostate tuberculosis may have non-specific symptoms and may be asymptomatic – in this case the disease is diagnosed accidentally. The frequency of prostate tuberculosis hiding under the mask of chronic prostatitis is high. Urogenital infections resistant to standard therapy are suspicious on tuberculosis.